Microplate assay for the determination of carboxypeptidase A inhibitory activity in Andean potatoes - Tellechea, Mariana Edith (2016)
Metallocarboxypeptidases (MCPs) are zinc-dependent exopeptidases that catalyze the hydrolysis of C-terminal amide bonds in proteins and peptides. MCPs are involved in a wide range of physiological processes and have recently emerged as relevant drug targets in biomedicine (Arolas et. al., 2007). In higher plants, small proteinaceous protease inhibitors are wound-induced molecules produced as a part of its defense system against insect attack (Graham et. al., 1981; Villanueva et. al. 1998). Among such inhibitors, only two are specific for MCPs, i.e. the potato carboxypeptidase inhibitor (PCI) and its close homologue found in tomato plants. In humans, MCP action is exquisitely regulated and dysregulation of their function might lead to disease or even to cell death (Arolas et. al., 2007). In this context, the discovery and characterization of new MCPs inhibitors constitute a valuable approach for the development of new therapeutic strategies. Over the last few decades, the presence of MCPs inhibitors in Solanaceae has been extensively reported, revealing potato (Solanum tuberosum) as one of the most important sources of MCPs inhibitors (Hass et. al.,1979; Lufrano et. al., 2015). In this context, potatos are native from the Andean region of South America, where thousands of different potato varieties coexist, constituting a natural reservoir for the discovery of novel MCP inhibitors (Figure 1). In this protocol, we describe an optimized, simple and accessible microplate method for the measure of the specific and dose-response carboxypeptidase A inhibitory activities present in Andean potatoes tubers.